Sistematização da assistência de enfermagem na rede de atenção básica de São Leopoldo : cuidados ao usuários com lesão de pele - Freitas, Lisane Nery (Universidade do Vale do Rio dos Sinos, 2019)
Skin lesions represent a public health problem in Brazil and worldwide. They represent a frequent demand in Primary Care (AB) and given the magnitude of the problem, the need to systematize nursing care for the prevention of skin lesions and the promotion of the healing process is highlighted, aiming at the recovery of the skin integrity of patients. users. The study aimed to implement the Nursing Care Systematization (SAE), in the care of the user with skin lesions, attended at the São Leopoldo / RS Health Care Network (RAS / SL). The theoretical framework of Theory of Wanda Horta was used to subsidize SAE. The design adopted was Thiollent'sresearch-action, developed in the scenario constituted by RAS / SL. Eight health professionals participated, six nurses, a pharmacist and a doctor. Initially, the main need of the participants was the creation of the São Leopoldo Skin Care Committee (CCPele-SL), carried out with support from the researcher; she participated in all meetings until the dissertation defense day, when a nursing professor / UNISINOS replaced her at CCPele-SL. Another decision by CCPele-SL was the mapping of users with skin lesions, seen at RAS / SL to identify their sociodemographic profile and the clinical characteristics of users' skin lesions. CCPele-SL counted on the researcher's support in the elaboration of the data collection instrument, educational material for the registration of information and data analysis. The 277 CCPele-SL records were included, related to the care of users with skin lesions, from May 21 to July 31, 2018. The results showed that of the 277 users evaluated, 57% were male and 36.83 % in the age group between 60 and 79 years. The most frequent skin injuries resulted from trauma and fracture (20.7%), venous ulcers (18.6%) and pressure injuries (16.3%); granulation tissue totaled 37.9% of the lesions; most located in the lower limbs (48.8%); 28% had Systemic Arterial Hypertension and 20.4% Diabetes Mellitus. From the data analysis, the Nursing Care Guide for prevention and treatment of skin lesions was elaborated, with procedural validation by CCPele-SL. A proposal for permanent health education was also drawn up, to present the Guide and involve nursing professionals in the SAE to the user with skin lesions, in the RAS / SL. The implementation of SAE will contribute to the improvement of nursing care provided to users with skin lesions, by directing and systematizing the stages of the care process, with scientific basis and an integral look at the individual. The results of this study gave rise to the following products: support for the creation of CCPele-SL; support in the mapping of users with skin lesions, seen at RAS / SL; development of support material to classify skin lesions; funding and preparation of the Wound Debridement Course, promoted by CCPele-SL; Nursing Care Guide for Prevention and Treatment of Skin Injuries; Proposed Permanent Health Education Program Plan for the nursing team on care for users with skin lesions. These products and, in particular, the entire process involving action research, have a positive impact on the nursing care / care scenario for users with skin lesions, in the RAS / SL.
Keywords: Cuidados de Enfermagem; Ferimentos e lesões; Atenção Primária à Saúde; Sistematização da Assistência de Enfermagem; Nursing care; Injuries and injuries; Primary Health Care; Systematization of Nursing Care; ACCNPQ::Ciências da Saúde::Enfermagem